2018
DOI: 10.1175/jcli-d-17-0308.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Extratropical Cyclone Precipitation in the North Atlantic Basin: An Analysis of ERA-Interim, WRF, and Two CMIP5 Models

Abstract: The representation of extratropical cyclones (ETCs) precipitation in general circulation models (GCMs) and a weather research and forecasting (WRF) model is analyzed. This work considers the link between ETC precipitation and dynamical strength and tests if parameterized convection affects this link for ETCs in the North Atlantic Basin. Lagrangian cyclone tracks of ETCs in ERA-Interim reanalysis (ERAI), the GISS and GFDL CMIP5 models, and WRF with two horizontal resolutions are utilized in a compositing analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 45 publications
6
37
1
Order By: Relevance
“…This implies that the corresponding emissions could have been triggered by easterlies on the northern flanks of the cyclones. Dust was hardly emitted from areas on the southern flanks of the cyclones which are commonly affected by fronts and precipitation (Booth et al, 2018). In addition to the dust emission areas that occurred equally during both regimes (cyclonic and east sector winds), the east sector winds also generated emissions in Austria, Slovakia, Hungary, Ukraine, central Germany, the Danube Basin and the North Sea Basin.…”
Section: Wind Regime-based Dust Cycle Decompositionmentioning
confidence: 98%
“…This implies that the corresponding emissions could have been triggered by easterlies on the northern flanks of the cyclones. Dust was hardly emitted from areas on the southern flanks of the cyclones which are commonly affected by fronts and precipitation (Booth et al, 2018). In addition to the dust emission areas that occurred equally during both regimes (cyclonic and east sector winds), the east sector winds also generated emissions in Austria, Slovakia, Hungary, Ukraine, central Germany, the Danube Basin and the North Sea Basin.…”
Section: Wind Regime-based Dust Cycle Decompositionmentioning
confidence: 98%
“…4 and the associated animation ES1 in the online supplemental material (https://doi.org/10.1175 /BAMS-D-19-0113.2). Reanalysisdriven RCM simulations are also commonly used in configuring and assessing a model with respect to the mean climate and phenomena of interest in a region (e.g., Booth et al 2018).…”
Section: Overview Of Experimental Designs and Scientific Questions Admentioning
confidence: 99%
“…GCMs need to capture the dynamics and thermodynamic properties of both the individual cyclone events and their accumulated behavior. Eulerian storm-track analysis revealed that model sea surface temperature biases impact the surface storm tracks and precipitation near ocean western boundary currents (Booth et al 2017;Small et al 2019). Targeted analyses of features in cyclones and/or their fronts were carried out using Lagrangian tracking algorithms and compositing.…”
Section: Fig 5 Scatterplots Between Cmip5 Models Simulated Precipitmentioning
confidence: 99%
“…10). Task force efforts on cyclone-centered precipitation led to 1) a satellite-based benchmarks (Naud et al 2019), and 2) results showing GCMs represent cyclone total precipitation as well as reanalysis, but the models have markedly different levels of contributions from their convection parameterizations (Booth et al 2018). The Lagrangian metrics require 6-hourly, three-dimensional data, some of which are not standard in the CMIP archive.…”
Section: Fig 5 Scatterplots Between Cmip5 Models Simulated Precipitmentioning
confidence: 99%